Quiet writing: Retreat as pedagogy - Keane, M. (South African Journal of Higher Education, 2017)
In a climate of increased pressure on academics to publish, some writing retreats have become crash-courses on writing, or bootcamps for getting words on paper. I argue for a pedagogy that deliberately aims to restore a sense of well-being in writers and draws on creative writing (Haarhoff 1998), situated within a paradigm of mindful inquiry (Bentz and Shapiro 1998). Based on observations, reflections and evaluations of 18 retreats run over the past six years for staff at a university in Johannesburg, I argue that the structure and process of the retreat is an integral part of the writing pedagogy. A retreat traditionally includes mindfulness, with a balance between effort and reflection. The writing retreat pedagogy I propose is a flow between being productive and restoring a sense of life-balance: quiet writing – meaning coming from a place of inner calm.